THE STUDY OF ADSORPTION ON Cr(VI) IN NATURAL CLAY SURFACE MODIFIED WITH SURFACTANT CTAB (Cetyltrimethylammonium Bromide) - Maksum Maksum; Susi Nurul Khalifah; Anton Prasetyo (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2014)
Clay is a mineral particles composed of silica-alumina base frame, has a layered structure and a hollowed space causing surface becomes very widespread and effective as an adsorbent. Adsorbent of clay is very effective to adsorb cation for having negatively charged surfaces, but its ability to adsorb anion is very low, such as Cr(VI) formed in HCrO4- at pH 2. This research has been conducted in the clay of activation process chemically with the variation of H2SO4 0,5, 1,0, 1,5 and 2,0 M and physically with the variation in the temperature of 200, 300, 400°C as well as modifying the surface with the variation of CTAB surfactant 25, 50, 75, and 100 mM to enhance the adsorption of Cr(VI). The results of study showed that the treatment on the activation and modification of natural clay can increase the adsorption capacity of Cr(VI) is greater. Adsorption capacity (Qe) before activating the natural clay is 0,0971 mg/g, while the Na-clay increased adsorption of Cr(VI) at 7,85 % as indicated by Qe = 0,1756 mg/g of natural clay. The use of 0,5 M H2SO4 activation of adsorption increased by 21,44 % to the value of Qe = 0,3115 mg/g. The treatment of physically activation after activating the best chemical showed at a temperature of 200°C with an increase of 29,82% adsorption of value Qe = 0,3953 mg/g. While modification to the clay treatment results in the best physical activation get CTAB 25 mM concentration with increased adsorption of 94,54 % with a value of Qe = 1,0425 mg/g.